People’s Perceptions of Factors Influencing the Language Effect in International Trade-Evidence from the Case of North Cyprus - Jaldi, Shiva (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
The main purpose of this thesis is to empirically investigate 25 factors of the language effects on foreign trade. 200 respondents, living at different areas, participated in the questionnaire. Means, Independent Samples Test, One-way Anova techniques were conducted to investigate and compare language effects criteria. According to the descriptive statistics, the most important factors compared to others are; ‘English language is the most useful one in international trade’, ‘easy learning’, ‘influence of colonial ties’ and ‘the effects of multi-language used at the same time in education system’. Based on independent sample t-test, ‘easy learning’, ‘influence of colonial ties’, ‘the effects of multi-language used at schools in a country at the same time’, ‘the level of gdp per capita (wealth of a nation)’, and ‘English language is the most useful one in international trade’, have differences between female and male on language effects in international trade. Finally, Anova analysis shows that “easy learning”, “influence of colonial ties”, “influence of the current technology development”, “effect of country educational system”, “the level of gdp per capita (wealth of a nation)”, “English language is the most useful one in international trade’ and ‘the effect of foreign language at schools in a country’ have differences based on the age groups in terms of influencing factors of the language effects in international trade. Keywords: language effect factors, independent sample-test, Anova analysis, North Cyprus economy

ÖZ: Bu tez yabancı dil faktörlerinin uluslararası ticaret üzerindeki önemini inceler. Kuzey Kıbrıs’ta 200 kişiyi hedef alarak yapılan bu çalışmada 25 önemli yabancı dil faktörünü içermektedir. Ortalama değerler, t-değerleri ve anova analizi hesaplanarak bu faktörlerin burada yaşayan kişiler üzerindeki etkisi mukayese edilmiştir. Ampirik Sonuçlar genel olarak yabancı dilin ‘kolay öğrenimi’, ‘koloni bağları’, ‘teknolojik gelişimin etkisi’, ‘ülkenin eğitim siteminin önemi’, ‘paralel zamanda ülkede kullanılan diğer yabancı dillerin etkisi’, ‘İngilizçe dilinin en kolay öğrenilir olması’ ve ‘kişi başı düşen milli gelirin’ etkisi en önemli nedenlerinden olduğunu göstermektedir. Bu kriterler statistiksel olarak anlamlı ve seçildiği cinsiyet ve yaş faktörleri bazında farklılık gözetmektedir. Anahtar Kelimeler: Yabancı dil kriterleri, t-testi, Anova analizi, Kuzey Kıbrıs Ekonomisi.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2014. Supervisor: Prof. Dr. Sami Fethi
Keywords: Business Administration; Marketing Management; International Business - Communication - Language; Language effect factors; independent sample-test; Anova analysis; North Cyprus economy